2008
DOI: 10.1073/pnas.0804793105
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between connexin35 and zonula occludens-1 and its potential role in the regulation of electrical synapses

Abstract: Although regulation of chemical transmission is known to involve the interaction of receptors with scaffold proteins, little is known about the existence of protein-protein interactions in regulating gap junction-mediated electrical synapses. The scaffold protein zonulaoccludens-1 (ZO-1), a member of the MAGUK family of proteins, was reported to interact with several connexins (Cxs). We show here that ZO-1 extensively colocalizes with Cx35 at identifiable ''mixed'' (electrical and chemical) contacts on goldfis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 49 publications
8
72
0
Order By: Relevance
“…Immunohistochemistry. Fish were perfused intracardially with saline phosphate buffer (1× PBS) at pH 7.2-7.4 for 10 min followed by cold 4% (wt/vol) formaldehyde in 0.1 M phosphate buffer (paraformaldehyde; PFA) for 10 min as previously described (31). Brains were dissected out and kept in 4% PFA overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry. Fish were perfused intracardially with saline phosphate buffer (1× PBS) at pH 7.2-7.4 for 10 min followed by cold 4% (wt/vol) formaldehyde in 0.1 M phosphate buffer (paraformaldehyde; PFA) for 10 min as previously described (31). Brains were dissected out and kept in 4% PFA overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…To examine trafficking further, we used a peptide corresponding to the last 15 amino acids of the CT of Cx36 (CT-peptide), a region that is identical to the CT of one fish homolog, Cx35, and has only minor differences from the CT of another, Cx34.7 ( Fig. 5A) (31). The peptide (1 mM) was included in the recording electrode solution, and both components of the EPSP were monitored.…”
Section: Interference With Endocytosis and Exocytosis Modifies Synapticmentioning
confidence: 99%
“…We first examined the localization of the electrical synapse scaffold ZO-1, which is known to interact through its PDZ domain with the C-terminus of Cx36[28]. We found that ZO-1 was colocalized with Cx36 within the M circuit as well as at other prominent electrical synapses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ZO-1 was originally identified as a tight junction-associated protein (Stevenson et al, 1986) and it belongs to the family of membrane-associated guanylate kinase homologs (MAGUKs) (for review, see González-Mariscal et al, 2000). More recently, ZO-1 was found to codistribute with gap junctions at cell-cell contacts, and to interact with Cx31.9, Cx43, Cx45, Cx46, and Cx50 via its second PDZ domain (for review, see Giepmans, 2004) and with Cx35/36 via the first PDZ domain (Li et al, 2004;Flores et al, 2008).…”
Section: Gap Junction Architecturementioning
confidence: 99%